Hospitality security : Managing security in today's hotel,lodging,entertainment and tourism environment - Clifton, Darrell (CRC Press, 2012)
"Written for those tasked with building a security department from the ground up, this book explains how to setup the department, how to determine and write policy, and how to keep even the most experienced professionals out of trouble and on top of their game. It provides information on criminal and civil law, risk management, budgeting and finance, labor relations, criminology, personnel management, training and education, written policy, safety, and health and other government standards. Case studies and best practices justify the reason for maintaining effective policies, purchasing new equipment, and managing a productive staff"--Provided by publisher.